Comparative evaluation of sealing ability of Zinc Oxide Eugenol and AH Plus sealers in laterally condensed gutta percha: A dye leakage study - Singh, Vimmi; Agrawal, Navin; Das, Murari Lal; Dangol, Ashok; Jain, Neetu; Dahal, Mona (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Airtight sealing of the root canal is the foremost desirable result of any root canal treatment, but getting the perfect filling of the root canal is always problematic, which could be due to multiple reasons. One such majorly reason impacting the obturation is the root canal sealer utilized. Objective: The present study was done for evaluating microleakage in zinc oxide eugenol cement (ZOE) and epoxy resin-based sealer (AH Plus) root canal sealers using linear dye leakage method. Methods: This in-vitro study used twenty-two extracted human single canal mandibular premolar teeth comprising 2 groups (11 in each), where sealers used for microleakage evaluation were ZOE cement sealer, and AH Plus. All the samples once cleaned, shaped and obturated were soaked in methylene blue dye for forty-eight hours with two millimeter (mm) exposed apex. The samples were then split into halves and inspected under a stereomicroscope for microleakage. The generated data were statistically analyzed using an independent t-test in SPSS version 11. Results: All the test samples showed microleakage. However, the mean microleakage measured was considerably higher in the ZOE cement sealer at 6.18mm and 2.95mm for the Epoxy resin-based sealer (AH Plus sealer). Conclusions: Epoxy resin-based sealer has better performance than ZOE cement sealer with minimal microleakage. Thus, Epoxy resin-based sealer showed a better prognosis and it can be considered to be adapted in clinical practice.